Chondrule Flattening by Shock Recovery Experiments on Unequilibrated Chondrites. Issue 8 (12th August 2021) - Miyahara, Masaaki; Edanaga, Junnosuke; Yamaguchi, Akira; Kobayashi, Takamichi; Sekine, Toshimori; Nakamura, Ayaka
Abstract: Shock recovery experiments were conducted using ALH‐78084 H3 and Y‐793375 L3 chondrites in the shock pressure range of 11–43 GPa to reproduce shock‐induced melting and chondrule flattening. Shock‐induced melt and chondrule flattening in 15 H3, 23 L3, and 23 LL3 ordinary chondrites were also investigated for comparisons. The shock experiments proved that, at least in unequilibrated ordinary chondrites, shock‐induced melting occurred beyond 11 GPa. The melting occurs at the boundary between chondrule and matrix. The melts included fine‐grained silicate minerals, glasses, and ameba or spherical metallic Fe–Ni or metallic Fe–Ni–iron sulfide with a eutectic texture that coincided with shock‐induced melts in the investigated H/L/LL3 ordinary chondrites. Shock experiments also proved that shock‐induced flattening of chondrules occurs and the flattening degree increases with increasing shock pressure. Considering the shock experiments not only of ordinary chondrites but also of carbonaceous chondrites, the flattening degree is not significantly affected by the density, porosity, and chondrule/matrix ratio of chondrites. The long axes of chondrules in shocked ALH‐78084 H3 and Y‐793375 L3 chondrites have preferred orientations and the degree increases with increasing shock pressure. It is difficult to estimate quantitatively the shock pressure recorded in unequilibrated ordinary chondrites using the empirical formula between the aspect ratio of chondrules and shock pressure. Nevertheless, the investigated L/LL3 ordinary chondrites with shock‐induced melts had higher aspect ratios (median, 1.36) and more strongly preferred orientations than those without shock‐induced melts (median, 1.25). Plain Language Summary: At an early stage, the ordinary chondrite parent body had an onion shell structure and an impact event disrupted it. Some ordinary chondrites that are derived from the surface of the parent body have a flattened chondrule and melting zone, which may be due to shock metamorphism. To reproduce shock‐induced melting and chondrule flattening, shock recovery experiments were conducted in the shock pressure range of 11–43 GPa using ordinary chondrites. Shock‐induced melting occurs at pressures above 11 GPa. The melting occurs at the boundary between a chondrule and the surrounding fine‐grained material. Shock‐induced flattening of chondrules occurs and the flattening degree increases with increasing shock pressure. The flattening degree is not significantly affected by differences in the density, porosity, and the chondrule/matrix ratios of the chondrites but depends simply on shock pressure. The long axes of chondrules have preferred orientations, the degree of which increases with increasing shock pressure. Key Points: Shock‐recovered H/L3 chondrites show melting onset at above 11 GPa and the flattening of chondrules increases at higher shock pressures No significant differences in the degree of chondrule flattening were found between carbonaceous and ordinary chondrites Chondrules in shock‐recovered chondrites present a preferred orientation with the degree increasing with increasing shock pressure